PEST analysis of a rankine organic cycle for energy recovery (2018)
In this work is presented a state of the art of political and economic investments, technological developments, social and environmental impacts of the 4 countries that contribute more research on the Organic Rankine Cycles (ORC) from the application of PEST analysis. Taking into account that technologies for waste heat recovery such as ORCs have been very popular due to their friendly impact on the environment. Countries such as the People's Republic of China are carrying out a large number of research projects on ORCs with industrial applications, and their policies are in line with the need to reduce greenhouse gas emissions, as evidenced by the Top-1000 Energy-Consuming Enterprises program, which seeks to optimize the systems of the country's main production companies.